A soap-free self-emulsifying alkyd-modified silicone resin and a method for preparing the same
Patent Information
- Application Number
- CN202611450013.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-27
AI Technical Summary
该路线的主要问题在于:烷氧基硅烷类单体在高温酯化缩聚条件下易发生水解缩合,若控制不当会导致体系凝胶或局部过度交联,漆膜均一性下降;同时,大量羧酸根离子残留在固化涂膜中形成亲水通道,损害长期耐水性
[0025](1)无皂自乳化:本发明通过GMA封端在醇酸树脂分子末端引入可聚合双键,再经硅氢加成反应将醇酸链段共价接枝到含氢苯基硅树脂上,形成具有两亲性分子结构的无皂自乳化树脂。醇酸链段中的羧基经中和后提供亲水性,含氢苯基硅树脂链段提供疏水性,二者通过共价键稳定连接,无需外加任何乳化剂即可在水中形成稳定的分散体,从根本上解决了外加乳化剂残留导致涂膜耐水性下降的问题。进一步地,通过控制中和度为70%~100%,既保证了树脂在水中的充分分散,又避免了过高含量的羧酸根离子残留于涂膜中损害耐水性。
Smart Images

Figure CN122978452A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer-modified silicone resin materials technology, specifically to a soap-free self-emulsifying alkyd modified silicone resin and its preparation method, as well as an aqueous coating using the silicone resin as a film-forming material. Background Technology
[0002] Alkyd resins have long held an important position in the coatings industry due to their wide availability of raw materials, low cost, high gloss, good adhesion, and excellent brushing performance. However, traditional solvent-based alkyd resin coatings contain a large amount of volatile organic compounds (VOCs), posing a threat to the environment and human health. With increasingly stringent environmental regulations, water-based formulations have become the main direction for the development of alkyd resins.
[0003] Existing waterborne alkyd resin waterborne technologies can be mainly divided into the following two categories: (a) Waterborne alkyd resin with added emulsifier This method disperses the resin in water by adding a small-molecule emulsifier. For example, Chinese invention patent CN112724421B discloses a method for preparing an alkyd resin emulsion, which involves adding a modified epoxy emulsifier to a vinyl silicone oil-modified alkyd resin, continuously stirring, and then adding water to disperse it evenly to obtain an emulsion. Another example is Chinese invention patent CN107488407B, which discloses an organosilicon-modified alkyd resin aqueous emulsion. This method involves reacting the alkyd resin with a hydrophilic modifier, then physically mixing it with an amphiphilic organosilicon modifier, and finally dispersing it under high shear to obtain an aqueous emulsion. In these methods, the added emulsifier remains in the coating film after film formation, forming hydrophilic channels and impairing the water resistance and gloss of the coating film.
[0004] (ii) Internally emulsified waterborne alkyd resin These methods achieve water solubility or self-emulsification by introducing hydrophilic groups (such as carboxyl groups) into the molecular chain and then neutralizing them to form salts. For example, US Patent 4069178A discloses a method for preparing a water-soluble organosilicon-modified alkyd resin. First, dehydrated castor oil fatty acids, pentaerythritol, phthalic anhydride, and other raw materials undergo esterification. Then, an organosilicon intermediate is added for co-condensation. Finally, more carboxyl groups are introduced with trimellitic anhydride, and water solubility is achieved through neutralization with amines to form salts. However, the patent specification clearly points out that gelation occurs during the reaction, indicating that the co-condensation process requires extremely stringent control of reaction conditions, making batch stability difficult to guarantee in industrial production. Furthermore, a large number of carboxyl groups remain in the cured coating after salt formation, impairing long-term water resistance. In addition, the organosilicon segments are connected to the alkyd backbone via Si-OC bonds, which pose a risk of hydrolysis in aqueous systems.
[0005] For example, Chinese invention patent CN104086761B proposes a waterborne organosilicon-modified alkyd resin and its preparation method. It uses unsaturated fatty oil, polyol, polyacid, and dimethylolpropionic acid (DMPA) as raw materials. During the alkyd polycondensation stage, organosilicon monomers (such as methyltriethoxysilane and phenyltriethoxysilane) are added, introducing organosilicon segments into the alkyd backbone through co-condensation. After neutralizing a large number of carboxyl groups with amines, waterborne properties are achieved. The main problem with this route is that alkoxysilane monomers are prone to hydrolysis and condensation under high-temperature esterification polycondensation conditions. Improper control can lead to gelation or excessive cross-linking in certain areas, reducing the uniformity of the coating film. Simultaneously, a large number of carboxylate ions remain in the cured coating, forming hydrophilic channels and impairing long-term water resistance. Chinese invention patent CN110776630B also introduces organosilicon components by adding vinyltrimethoxysilane or vinyltriethoxysilane during the alkyd polycondensation stage, but it still suffers from the inherent defects of the co-condensation route mentioned above. For example, Chinese invention patent CN105348498B reported a technical solution for introducing organosilicon segments by reacting epoxy organosilicon alkane with the alcohol hydroxyl and carboxyl groups in alkyd resin. However, the introduction of organosilicon also depends on co-condensation or ring-opening reaction, making it difficult to precisely control the grafting position and degree.
[0006] Chinese invention patent application CN119176917A discloses another method for preparing organosilicon-modified waterborne alkyd resin dispersions. First, an alkyd ester containing vinyl double bonds and a double-bond modified organosilicon prepolymer are synthesized. Then, vinyl monomers are mixed with the modified organosilicon prepolymer and copolymerized via free radical polymerization. Waterborne polymerization is achieved by neutralizing carboxyl groups with amines in a large amount of alcohol ether solvent. The main problems with this method are: side reactions such as homopolymerization and crosslinking are difficult to control during free radical polymerization; multiple polymerizable double bonds exist in the reaction system with large differences in polymerization reactivity, making precise control of the copolymer composition difficult; the use of large amounts of alcohol ether solvents leads to high VOC content in the final product; and the process route is complex and involves many steps, increasing the cost of industrial production.
[0007] Chinese invention patent, publication number CN104927039B, reports a silicone-modified alkyd resin. It involves reacting terminal hydroxyl aliphatic hyperbranched polyester with crude cottonseed oil, pentene, and silicone monomers in xylene solvent. The resulting product is still a solvent-based system and cannot be water-based.
[0008] In summary, the existing technology still faces the following unresolved technical challenges: First, there is a contradiction between water-based properties and coating performance. Existing methods, whether using external emulsifiers or introducing large amounts of hydrophilic monomers, sacrifice the water resistance, gloss, and mechanical properties of the coating. How to achieve stable water dispersion without adding external emulsifiers and without excessive reliance on hydrophilic monomers is a pressing technical challenge in this field.
[0009] Second, there is the issue of compatibility between alkyd resins and silicone resins. The two have significant polarity differences, and physical blending can easily lead to macroscopic phase separation. Although co-condensation can form chemical bonds, it involves the hydrolysis equilibrium of Si-OC or Si-O-Si bonds, the reaction conditions are harsh, and the grafting position and extent are difficult to control precisely.
[0010] Third, there is the problem of limited oxygen diffusion during the air-drying curing process. The curing of air-drying alkyd resins depends on oxygen diffusion into the coating film to undergo oxidative cross-linking with the fatty acid double bonds. When the coating thickness exceeds 40–60 μm, oxygen has difficulty diffusing to the underlying layers, resulting in slow deep curing and the technical problem of "dry on the surface but not inside." Existing waterborne alkyd resin technologies have not effectively solved the problem of thick film curing. For example, although Chinese invention patent CN110776630B introduces organosilicon to improve weather resistance, it does not address the promoting effect of oxygen permeability on the curing rate.
[0011] Fourth, there is a lack of mild and highly selective chemical grafting pathways. In existing technologies, the introduction of organosilicon mainly relies on co-condensation or free radical copolymerization. The former involves the risk of hydrolysis and condensation, while the latter involves the challenge of controlling side reactions.
[0012] Therefore, there is currently a lack of a waterborne alkyd-modified silicone resin system that does not require the addition of external emulsifiers and simultaneously solves the problems of compatibility between alkyd and organosilicon and thick film curing. Summary of the Invention
[0013] To overcome the aforementioned technical problems, this invention provides a soap-free self-emulsifying alkyd modified silicone resin, its preparation method, and its application. By introducing double bonds through GMA end-capping and a platinum-catalyzed hydrosilylation grafting chemical pathway to hydrogen-containing phenyl silicone resin, a covalently linked amphiphilic graft copolymer is constructed. At the same time, the high oxygen permeability of the organosilicon segments is utilized to accelerate the deep curing of the coating, fundamentally solving the above-mentioned technical difficulties.
[0014] The technical solutions to the above technical problems are as follows: A method for preparing a soap-free, self-emulsifying alkyd-modified silicone resin includes the following steps: S1: Synthetic waterborne alkyd resin prepolymer with terminal carboxyl groups is obtained by using vegetable oil, trimethylolpropane, and polybasic acid anhydrides as raw materials, through alcoholysis and esterification polycondensation reactions, yielding a short-oil alkyd resin prepolymer with an acid value of 50-60 mg KOH / g; specifically: Vegetable oil, trimethylolpropane, and lithium hydroxide were added to a reaction vessel and heated to 220–240°C under inert gas protection for alcoholysis. After alcoholysis, the temperature was lowered to 160–180°C, and polyacid anhydrides, xylene, and antioxidants were added. The temperature was then raised to 180–220°C for esterification and polycondensation. The reaction was stopped when the acid value of the reaction system dropped to 50–60 mg KOH / g and the number-average molecular weight determined by gel permeation chromatography reached 900–1300.
[0015] Specifically, the vegetable oil is either linseed oil or dehydrated castor oil; the amount of lithium hydroxide added is 0.01% to 0.05% of the total mass of the reactants. The method for determining the endpoint of alcoholysis is as follows: mix the alcoholysis solution with 87% ethanol at a mass-volume ratio of 1:5 to 1:7. When the solution becomes transparent and there is no layering, the alcoholysis is complete.
[0016] The polybasic acid anhydride is a mixture of phthalic anhydride and trimellitic anhydride; the mass ratio of vegetable oil, trimethylolpropane, phthalic anhydride, and trimellitic anhydride is 30-45:25-35:15-25:5-12.
[0017] The amount of xylene added is 3% to 8% of the total mass of the reactants; The antioxidant is either triphenyl phosphite or hydroquinone, and its addition amount is 0.05% to 0.2% of the total mass of the reactants.
[0018] S2: GMA end-capping introduces polymerizable double bonds. The epoxy groups of GMA react with the terminal carboxyl groups of the alkyd prepolymer, undergoing ring-opening esterification to introduce polymerizable C=C double bonds at the ends of the alkyd molecular chains; specifically: Add a polymerization inhibitor to the aqueous alkyd resin prepolymer obtained in step S1 and stir until homogeneous; mix glycidyl methacrylate with the catalyst and add it dropwise to the reaction system, keep the reaction at 100-110℃, and stop the reaction when the acid value drops to below 10mgKOH / g to obtain GMA-terminated aqueous alkyd resin. Furthermore, the polymerization inhibitor is p-hydroxyanisole (MEHQ), and its addition amount is 0.1% to 0.5% of the mass of glycidyl methacrylate; the catalyst is N,N-dimethylbenzylamine, and its addition amount is 0.1% to 0.5% of the total mass of the aqueous alkyd resin prepolymer obtained in step S1; the addition amount of glycidyl methacrylate is 1.0 to 1.2 times the number of carboxyl groups in the alkyd resin prepolymer obtained in step S1.
[0019] S3: Hydrosilylation grafting reaction. GMA-terminated alkyd resin and hydrogen-containing phenyl silicone resin are subjected to a Si-H and C=C hydrosilylation reaction under a platinum catalyst, covalently grafting alkyd segments onto organosilicon segments. After neutralization and phase inversion dispersion, a soap-free, self-emulsifying alkyd-modified silicone resin dispersion is obtained. Specifically: The GMA-terminated aqueous alkyd resin obtained in step S2 was dissolved in a solvent, and hydrogen-containing phenyl silicone resin and platinum catalyst were added. The mixture was heated to 80–120 °C to carry out a hydrosilylation reaction. The Si-H bond at 2160 cm⁻¹ was tracked by infrared spectroscopy. -1 The C=C bond is located at 1640 cm. -1 The disappearance of the characteristic peaks determines the reaction endpoint. After the reaction is complete, the solvent is removed, and a neutralizing agent and deionized water are added for phase inversion dispersion to obtain a soap-free self-emulsifying alkyd modified silicone resin dispersion. This silicone resin dispersion is an amphiphilic graft copolymer, with hydrophilic segments being carboxyl-containing aqueous alkyd segments and hydrophobic segments being hydrogen-containing phenyl silicone resin segments. It can self-emulsify and disperse in water without the addition of external emulsifiers.
[0020] Furthermore, the hydrogen content of the hydrogen-containing phenyl silicone resin is 0.1wt% to 1.0wt%, the phenyl content is 10wt% to 40wt%, and the molar ratio of C=C in Si-H and GMA-terminated waterborne alkyd resin is 1.0 to 1.5:1.0.
[0021] Furthermore, the platinum catalyst is either a Karstedt-type or a Speier-type platinum catalyst, and its dosage is 5 to 50 ppm of the total mass of the reactants.
[0022] Furthermore, the neutralizing agent is either triethylamine or 2-amino-2-methyl-1-propanol, with a neutralization degree of 70% to 100%. The neutralization degree refers to the molar percentage of neutralized carboxyl groups relative to all carboxyl groups contained in the grafting reaction product in step S3.
[0023] Another object of the present invention is to provide a coating formulation containing a soap-free self-emulsifying alkyd-modified silicone resin dispersion prepared by the above method, comprising a soap-free self-emulsifying alkyd-modified silicone resin dispersion, a drier, a defoamer, a wetting and dispersing agent, pigments and / or fillers, a thickener, and deionized water; wherein the mass ratio of the soap-free self-emulsifying alkyd-modified silicone resin dispersion to deionized water is 100:5-20. The drier is one or more combinations of cobalt isooctanoate, zirconium isooctanoate, calcium naphthenate, and zinc isooctanoate, and its addition amount is 0.2%-1% of the mass of the soap-free self-emulsifying alkyd-modified silicone resin dispersion; the defoamer is one of a polyether-modified polysiloxane defoamer or a non-silicone defoamer, and its addition amount is 0.1%-0.5% of the mass of the soap-free self-emulsifying alkyd-modified silicone resin dispersion; the wetting and dispersing agent is one of a nonionic, anionic, or polymeric wetting and dispersing agent. The additive is 0.3% to 1% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion; the pigment and / or filler is one or more of titanium dioxide, iron oxide red, talc, and precipitated barium sulfate, and its addition amount is 10% to 40% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion; the thickener is one of cellulose ethers, alkali-swellable thickeners, or polyurethane thickeners, and its addition amount is 0.1% to 0.5% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion.
[0024] The preparation method of the above coating includes the following steps: mixing soap-free self-emulsifying alkyd modified silicone resin dispersion with pigments and / or fillers, wetting and dispersing agents, and a portion of deionized water, and grinding to a fineness ≤30μm; adding a drier, defoamer, thickener, and the remaining deionized water in sequence under stirring, and stirring evenly; adjusting the pH to 7.5-8.5 with a neutralizing agent, filtering out the material, and sealing and packaging to obtain an air-drying coating that is cured into a film by oxygen oxidation crosslinking at room temperature. The beneficial effects of this invention are:
[0025] (1) Soap-free self-emulsification: This invention introduces polymerizable double bonds at the ends of alkyd resin molecules through GMA end-capping, and then covalently grafts the alkyd segments onto hydrogen-containing phenyl silicone resin via hydrosilylation reaction, forming a soap-free self-emulsifying resin with an amphiphilic molecular structure. The carboxyl groups in the alkyd segments provide hydrophilicity after neutralization, while the hydrogen-containing phenyl silicone resin segments provide hydrophobicity. The two are stably linked by covalent bonds, forming a stable dispersion in water without the need for any external emulsifier, fundamentally solving the problem of reduced water resistance of the coating film caused by residual external emulsifiers. Furthermore, by controlling the degree of neutralization to 70%–100%, both sufficient dispersion of the resin in water and avoidance of excessive carboxylate ions remaining in the coating film, which would damage water resistance.
[0026] (2) Covalent bond connection, excellent compatibility: The two-step chemical bonding route adopted in this invention, namely alkyd synthesis, GMA end capping, and hydrosilylation grafting, solves the problem of poor compatibility between alkyd resin and organosilicon resin. The alkyd segment and the organosilicon segment are stably connected by covalent bonds, and no macroscopic phase separation occurs. The coating uniformity and performance repeatability are significantly better than those of the physical blend system.
[0027] (3) Accelerated Deep Curing: The organosilicon segments have an extremely high oxygen permeability coefficient (PDMS has an oxygen permeability coefficient of approximately 600 Barrer, which is hundreds of times that of conventional alkyd resins), which can significantly accelerate the diffusion rate of oxygen into the interior during the coating curing process, improve the deep curing effect, and reduce the actual drying time to only 3.5 to 5 hours, while the actual drying time of commercially available products with added emulsifiers is 8 hours, a reduction of 30% to 50%. This is especially suitable for thick film coating scenarios and effectively solves the technical problem of "surface drying but internal not drying" in traditional air-drying alkyd coatings. The relatively uniform drying speed inside and outside also helps to improve the appearance of the paint film and reduce the risk of wrinkling.
[0028] (4) Excellent overall performance: Alkyd segments ensure good adhesion and high gloss to substrates such as metal and wood; silicone segments give the coating excellent weather resistance, flexibility and hydrophobicity, and the two complement each other.
[0029] (5) Mild and controllable process: It does not involve high temperature, high pressure or highly toxic reagents, the raw materials are widely available and the cost is controllable, making it suitable for industrial production. Attached Figure Description
[0030] Figure 1 The infrared spectrum of the GMA-terminated waterborne alkyd resin obtained in step S2 of Example 1 of this invention is shown.
[0031] Figure 2 The infrared spectrum of the hydrogen-containing phenyl silicone resin obtained in step S3 of Example 1 of the present invention is shown.
[0032] Figure 3 The infrared spectrum of the soap-free self-emulsifying alkyd modified silicone resin obtained in step S3 of Example 1 of the present invention is shown. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.
[0034] Unless otherwise specified, all reagents and raw materials used in the following examples are commercially available, and their specific sources are not detailed. In the following examples, unless otherwise specified, "parts" refers to parts by weight. In this invention, the degree of neutralization refers to the percentage of moles of carboxyl groups neutralized by the added neutralizing agent relative to the total number of moles of carboxyl groups in the resin. In each example, the total number of moles of carboxyl groups in the resin is calculated based on the measured acid value, and then the required amount of neutralizing agent is calculated according to the set degree of neutralization. Example 1:
[0035] S1: Synthetic aqueous alkyd resin prepolymer with terminal carboxyl groups: In a reaction vessel equipped with a stirrer, a temperature device, a water separator with a condenser, and a nitrogen inlet pipe, add 30g of linseed oil, 30g of trimethylolpropane, and 0.018g of lithium hydroxide. Heat to 120°C under nitrogen protection to melt the system, and continue to raise the temperature to 240°C. Maintain this temperature for alcoholysis for about 1.5 hours. Take a small amount of the alcoholysis solution and determine the tolerance with 87% ethanol. When the ratio reaches 1:6 (1g alcoholysis solution: 6mL ethanol), the alcoholysis is considered successful.
[0036] After alcoholysis, the temperature was lowered to 180℃. 20g of phthalic anhydride, 5g of trimellitic anhydride, 6g of xylene for reflux, and 0.1g of triphenyl phosphite were added to the reaction system. The system temperature was controlled at 180℃~220℃, and stable reflux was maintained to carry out the esterification and polycondensation reaction. Water generated during the esterification reaction was continuously separated using a water separator. Sampling was performed periodically to determine the acid value and viscosity. Heating was stopped when the acid value of the reaction system dropped to 55mg KOH / g and the number-average molecular weight reached 900~1300. The system was then cooled to 105℃ for later use. S2: GMA end capping introduces aggregateable double bonds: Based on the measured acid value (55 mg KOH / g) of the 50 g aqueous alkyd resin prepolymer obtained in step S1, calculate the molar number of carboxyl groups. Add GMA (approximately 7.6 g) at 1.1 times the molar number of carboxyl groups. First, add 0.3% (by weight) of MEHQ polymerization inhibitor (approximately 0.023 g) of GMA to the aqueous alkyd resin prepolymer at 105℃ and stir until homogeneous.
[0037] 7.6 g of GMA and 0.2 g of N,N-dimethylbenzylamine catalyst were mixed thoroughly and slowly added dropwise to the reaction system over 30 minutes using a constant-pressure dropping funnel. After the addition was complete, the system temperature was raised to 105 ± 0.5 °C and maintained for reaction. The acid value was measured every 30 minutes. After approximately 2 hours, the acid value dropped to 8 mg KOH / g, indicating the end of the reaction. The mixture was then cooled to 80 °C and discharged to obtain GMA-terminated waterborne alkyd resin. Its infrared spectrum is attached. Figure 1 As shown.
[0038] Figure 1 Mid-infrared characteristic absorption peak: 3200~3600cm-1 The stretching vibration peak at 2925 cm⁻¹ is attributed to the residual hydroxyl group (-OH) in the resin molecule. -1 The saturated CH (-CH2-, -CH3) stretching vibration peaks, belonging to the long-chain alkyl and fatty acid segments of alkyd resins, are located at 1728 cm⁻¹. -1 The strongest characteristic peak of the system, at 1640 cm⁻¹, is attributed to the C=O stretching vibration of the alkyd main chain polyester bond and the superposition of the methacrylate carbonyl group introduced by GMA. -1 The peak at 1455 cm⁻¹ belongs to the C=C carbon-carbon double bond stretching vibration in the GMA structure. -1 Attributable to alkyl CH and methyl bending vibrations, 1245 cm⁻¹ -1 The characteristic COC stretching vibration peak, 750 cm⁻¹, belongs to the alkyd polyester skeleton. -1 It belongs to the stretching vibration peak of long-chain alkyl groups.
[0039] S3: Hydrosilylation grafting reaction: 20g of the GMA-terminated aqueous alkyd resin obtained in step S2 was dissolved in 30g of xylene. 4.5g of hydrogen-containing phenyl silicone resin (Si-H to C=C molar ratio in the GMA-terminated aqueous alkyd resin was 1.3:1.0) with a hydrogen content of 0.1wt% and a phenyl content of 25wt% was added, along with 50ppm of a Karstedt-type catalyst. The mixture was heated to 100℃ for a hydrosilylation reaction. After approximately 2 hours of holding at this temperature, the Si-H bond was tracked by infrared spectroscopy at 2160 cm⁻¹. -1 The C=C bond is located at 1640 cm. -1 The disappearance of the characteristic peaks determined the reaction endpoint. After the reaction was completed, the solvent was removed by vacuum distillation. The infrared spectrum is shown in the attached figure. Figure 2 As shown.
[0040] Figure 2 Mid-infrared characteristic absorption peak: 3300 cm⁻¹ -1 The peak at 3070 cm⁻¹ belongs to the stretching vibration of the residual hydrophilic hydroxyl group (-OH) in the aqueous alkyd chain. -1 The peak is attributed to the stretching vibration of the unsaturated CH on the phenyl ring, at 2960 cm⁻¹. -1 The peak at 2160 cm⁻¹ belongs to the stretching vibration of alkyl groups in alkyd and methyl groups in silicone resins. -1 The characteristic Si-H absorption peak at 1730 cm⁻¹ belongs to phenyl silicone resin. -1 The C=O stretching vibration peak of methacrylate, attributed to the alkyd main chain polyester C=O and introduced by GMA end capping, is located at 1600–1420 cm⁻¹. -1 Attributable to multiple splitting peaks of the C=C stretching vibration of the benzene ring skeleton, 1050 cm⁻¹ -1 It belongs to the stretching vibration of the Si-O-Si silicon-oxygen framework and is a characteristic broad and strong absorption band of the phenyl silicone resin backbone, ranging from 740 to 702 cm⁻¹.-1 It is attributed to the out-of-plane bending vibration peak of monosubstituted phenyl CH.
[0041] Based on the acid value of the grafted product obtained in step S3 (approximately 8 mg KOH / g), the molar number of carboxyl groups was calculated. The required amount of neutralizing agent was calculated based on a neutralization degree of 80%. 0.3 g of triethylamine was added for neutralization. After stirring for 10 minutes, 50 g of deionized water was slowly added under high-speed shear for phase inversion dispersion. Stirring was continued for 30 minutes to obtain a soap-free, self-emulsifying alkyd-modified silicone resin dispersion with a solid content of approximately 40%. The average particle size was determined by dynamic light scattering method to be approximately 200 nm. Its infrared spectrum is attached. Figure 3 As shown.
[0042] Figure 3 Mid-infrared characteristic absorption peak: 3300 cm⁻¹ -1 The absorption peak at 3070 cm⁻¹ is attributed to the superposition of the stretching vibrations of the hydrophilic hydroxyl group (-OH) of the resin and the neutralized ammonium carboxylate salt (NH). -1 The peak at 2960 cm⁻¹ belongs to the unsaturated CH stretching vibration of the benzene ring in phenyl silicone resin. -1 The peak at 2160 cm⁻¹ belongs to the stretching vibration of long-chain alkyl and organosilicon methyl groups in alkyd vegetable oils, specifically the CH (-CH₃, -CH₂-) stretching vibration. -1 The characteristic Si-H absorption peak at 1730 cm⁻¹ belongs to phenyl silicone resin. -1 The peak at 1600 cm⁻¹ belongs to the superimposed stretching vibration of the C=O ester bond in the main chain of alkyd polyester and the carbonyl group of the GMA-terminated acrylate. -1 Characteristic peaks attributable to the symmetric / asymmetric stretching vibrations of COO⁻ in ammonium carboxylate salts, 1590–1490 cm⁻¹ -1 The peak at 1050 cm⁻¹ belongs to the C=C splitting vibration of the benzene ring skeleton in phenyl silicone resin. -1 The peaks are attributed to the stretching vibrations of the Si-O-Si organosilicon-oxygen framework, and are superimposed with the stretching vibrations of the COC ether bonds in alkyd polyesters, ranging from 740 to 705 cm⁻¹. -1 The peaks are attributed to the out-of-plane bending vibrations of monosubstituted phenyl CH and the out-of-plane bending vibrations of long-chain methylene groups in vegetable oil.
[0043] Coatings were prepared using the soap-free self-emulsifying alkyd-modified silicone resin dispersion obtained in step S3. Take 100g of soap-free self-emulsifying alkyd modified silicone resin dispersion, add 10.0g of titanium dioxide, 0.5g of nonionic wetting and dispersing agent and 5g of deionized water and mix. Disperse in a high-speed disperser until the fineness is ≤30μm. While stirring, add 0.4g of cobalt isooctanoate (6% cobalt content), 0.3g of zirconium isooctanoate (12% zirconium content), 0.2g of polyether modified polysiloxane defoamer and 5g of deionized water in sequence and stir evenly. Add 0.1g of cellulose ether thickener to adjust the viscosity, adjust the pH to 8.0 with triethylamine, filter through a 200-mesh filter and seal and package to obtain an air-drying coating that is cured into a film by oxygen oxidation crosslinking at room temperature. Example 2:
[0044] S1: Synthetic aqueous alkyd resin prepolymer with terminal carboxyl groups: In a reaction vessel equipped with a stirrer, a temperature device, a water separator with a condenser, and a nitrogen inlet pipe, add 40g of dehydrated castor oil, 35g of trimethylolpropane, and 0.008g of lithium hydroxide. Heat to 120°C under nitrogen protection to melt the system, and continue to raise the temperature to 220°C. Maintain this temperature for alcoholysis for about 2.5 hours. Take a small amount of the alcoholysis liquid and determine the tolerance with 87% ethanol. When the tolerance reaches 1:5 (1g alcoholysis liquid: 5mL ethanol), the alcoholysis is qualified.
[0045] After alcoholysis, the temperature was lowered to 200℃. 25g phthalic anhydride, 8g trimellitic anhydride, 3g xylene for reflux, and 0.05g triphenyl phosphite were added to the reaction system. The system temperature was controlled at 180℃~220℃, and stable reflux was maintained to carry out the esterification and polycondensation reaction. Water generated during the esterification reaction was continuously separated using a water separator. Sampling was performed periodically to determine the acid value and viscosity. Heating was stopped when the acid value of the reaction system dropped to 50mg KOH / g and the number-average molecular weight reached 900~1300. The system was then cooled to 100℃ for later use. S2: GMA end capping introduces aggregateable double bonds: Based on the measured acid value (50 mg KOH / g) of the 50 g aqueous alkyd resin prepolymer obtained in step S1, calculate the number of carboxyl groups in molars. Add GMA (approximately 6.3 g) at 1.0 times the number of carboxyl groups in molars. First, add 0.5% (by weight) of MEHQ polymerization inhibitor (approximately 0.032 g) of GMA to the aqueous alkyd resin prepolymer at 100°C and stir until homogeneous.
[0046] 6.3 g of GMA and 0.25 g of N,N-dimethylbenzylamine catalyst were mixed thoroughly and slowly added dropwise to the reaction system over 30 minutes using a constant-pressure dropping funnel. After the addition was complete, the system temperature was raised to 100 ± 0.5 °C and maintained for reaction. The acid value was measured every 30 minutes; after approximately 2 hours, the acid value dropped to 8 mg KOH / g, indicating the end of the reaction. The mixture was then cooled to 80 °C and discharged to obtain GMA-terminated waterborne alkyd resin.
[0047] S3: Hydrosilylation grafting reaction: 20g of the GMA-terminated aqueous alkyd resin obtained in step S2 was dissolved in 30g of xylene. 3.2g of hydrogen-containing phenyl silicone resin (Si-H to C=C molar ratio in the GMA-terminated aqueous alkyd resin was 1.0:1.0) with a hydrogen content of 0.5wt% and a phenyl content of 40wt% was added, along with 30ppm of a Speier-type catalyst. The mixture was heated to 80℃ for a hydrosilylation reaction. After approximately 2.5 hours of holding at this temperature, the Si-H bond was tracked by infrared spectroscopy at 2160 cm⁻¹. -1 The C=C bond is located at 1640 cm. -1 The disappearance of the characteristic peak at the reaction point determines the reaction endpoint. After the reaction is complete, the solvent is removed by vacuum distillation.
[0048] Based on the acid value of the grafted product obtained in step S3 (approximately 8 mg KOH / g), the number of carboxyl groups was calculated. The amount of neutralizing agent required was calculated based on a neutralization degree of 100%. 0.3 g of 2-amino-2-methyl-1-propanol (AMP) was added for neutralization. After stirring for 10 minutes, 50 g of deionized water was slowly added under high-speed shear for phase inversion dispersion. Stirring was continued for 30 minutes to obtain a soap-free self-emulsifying alkyd modified silicone resin dispersion with a solid content of approximately 38%. The average particle size was approximately 180 nm as determined by dynamic light scattering.
[0049] Coatings were prepared using the soap-free self-emulsifying alkyd-modified silicone resin dispersion obtained in step S3. Take 100g of soap-free self-emulsifying alkyd modified silicone resin dispersion, add 20g of iron oxide red, 5g of talc, 0.3g of anionic wetting and dispersing agent and 15g of deionized water and mix. Disperse in a high-speed disperser until the fineness is ≤30μm. While stirring, add 0.5g of cobalt isooctanoate, 0.5g of calcium naphthenate (4% calcium content), 0.1g of polyether modified polysiloxane defoamer and 5g of deionized water in sequence and stir evenly. Add 0.5g of alkali-swellable thickener to adjust the viscosity. Adjust the pH to 8.2 with 2-amino-2-methyl-1-propanol (AMP). Filter through a 200-mesh filter and seal the product to obtain an air-drying coating that cures into a film by oxygen oxidation crosslinking at room temperature. Example 3:
[0050] S1: Synthetic aqueous alkyd resin prepolymer with terminal carboxyl groups: In a reaction vessel equipped with a stirrer, a temperature device, a water separator with a condenser, and a nitrogen inlet pipe, add 45g of linseed oil, 25g of trimethylolpropane, and 0.035g of lithium hydroxide. Heat to 120°C under nitrogen protection to melt the system, and continue to raise the temperature to 230°C. Maintain this temperature for alcoholysis for about 2 hours. Take a small amount of the alcoholysis solution and determine the tolerance with 87% ethanol. When the tolerance reaches 1:7 (1g alcoholysis solution: 7mL ethanol), the alcoholysis is qualified.
[0051] After alcoholysis, the temperature was lowered to 190℃. 15g phthalic anhydride, 12g trimellitic anhydride, 8g xylene for reflux, and 0.2g hydroquinone were added to the reaction system. The system temperature was controlled at 180℃~220℃, and stable reflux was maintained to carry out the esterification and polycondensation reaction. Water generated during the esterification reaction was continuously separated using a water separator. Sampling was performed periodically to determine the acid value and viscosity. Heating was stopped when the acid value of the reaction system dropped to 60mg KOH / g and the number-average molecular weight reached 900~1300. The system was then cooled to 100℃ for later use. S2: GMA end capping introduces aggregateable double bonds: Based on the measured acid value (60 mg KOH / g) of the 50 g aqueous alkyd resin prepolymer obtained in step S1, calculate the number of carboxyl groups in molars. Add GMA (approximately 9.1 g) at 1.2 times the number of carboxyl groups in molars. First, add 0.1% (by weight) of MEHQ polymerization inhibitor (approximately 0.009 g) of GMA to the aqueous alkyd resin prepolymer at 110℃ and stir until homogeneous.
[0052] 9.1 g of GMA and 0.05 g of N,N-dimethylbenzylamine were mixed thoroughly and slowly added dropwise to the reaction system over 30 minutes using a constant-pressure dropping funnel. After the addition was complete, the system temperature was raised to 110 ± 0.5 °C and maintained for reaction. The acid value was measured every 30 minutes; after approximately 2 hours, the acid value dropped to 10 mg KOH / g, indicating the end of the reaction. The mixture was then cooled to 80 °C and discharged to obtain GMA-terminated waterborne alkyd resin.
[0053] S3: Hydrosilylation grafting reaction: 20g of the GMA-terminated aqueous alkyd resin obtained in step S2 was dissolved in 30g of xylene. 6.0g of hydrogen-containing phenyl silicone resin (Si-H to C=C molar ratio in the GMA-terminated aqueous alkyd resin was 1.5:1.0) with a hydrogen content of 1.0wt% and a phenyl content of 10wt% was added, along with 5ppm of Karstedt-type catalyst. The mixture was heated to 120℃ for a hydrosilylation reaction. After approximately 3 hours of holding at this temperature, the Si-H bond was tracked by infrared spectroscopy at 2160 cm⁻¹. -1 The C=C bond is located at 1640 cm. -1 The disappearance of the characteristic peak at the reaction point determines the reaction endpoint. After the reaction is complete, the solvent is removed by vacuum distillation.
[0054] Based on the acid value of the grafted product obtained in step S3 (approximately 10 mg KOH / g), the number of carboxyl groups was calculated. The amount of neutralizing agent required was calculated based on a neutralization degree of 70%. 0.33 g of triethylamine was added for neutralization. After stirring for 10 minutes, 50 g of deionized water was slowly added under high-speed shearing for phase inversion dispersion. Stirring was continued for 30 minutes to obtain a soap-free self-emulsifying alkyd modified silicone resin dispersion with a solid content of approximately 42%. The average particle size was approximately 230 nm as determined by dynamic light scattering.
[0055] Coatings were prepared using the soap-free self-emulsifying alkyd-modified silicone resin dispersion obtained in step S3. Take 100g of soap-free self-emulsifying alkyd modified silicone resin dispersion, add 40g of precipitated barium sulfate, 1.0g of polymeric wetting and dispersing agent and 3g of deionized water and mix. Disperse in a high-speed disperser until the fineness is ≤30μm. While stirring, add 0.1g of cobalt isooctanoate, 0.1g of zinc isooctanoate, 0.5g of non-silicone defoamer and 2g of deionized water in sequence and stir evenly. Add 0.25g of polyurethane thickener to adjust the viscosity, adjust the pH to 7.8 with triethylamine, filter through a 200-mesh filter and seal and package to obtain an air-drying coating that is cured into a film by oxygen oxidation crosslinking at room temperature. Comparative Example 1:
[0056] To further verify the performance advantages of the soap-free self-emulsifying alkyd modified silicone resin of the present invention, the commercially available silicone resin modified alkyd emulsion product WorléeSol SE 420 W (manufactured by Worlée-Chemie GmbH, Germany) was used as a comparative example for performance comparison.
[0057] WorléeSol SE 420 W is a medium-oil, silicone-modified alkyd emulsion. Its main technical parameters are: solid content 40%±2, oil content approximately 42%, acid value (for solid resin) maximum 30 mg KOH / g, pH value 7.0~8.5, viscosity (20°C) maximum 5000 mPa·s, and silicone resin content approximately 24%. This product achieves waterborne dispersion of the resin through the addition of an emulsifier, and belongs to a typical waterborne alkyd resin with added emulsifier. Performance Testing and Analysis The performance of commercially available WorléeSol SE 420 W (Comparative Example 1) and the coatings obtained in Examples 1 to 3 were tested according to the same coating formulation and test method as in Example 1. The test items, test methods and test results are shown in Table 1.
[0058] Table 1. Coating performance test data obtained from Comparative Example 1 and Examples 1-3 ; [1] The coating thickness of the test sample was 100 μm. As can be seen from the performance test data in Table 1, the coatings prepared in Examples 1 to 3 have the appearance of a uniform emulsion system. None of the three groups showed any layering, clumping, or precipitation. The emulsion dispersion stability was good, which means that by using GMA to end-cap the alkyd segments (containing -COOH, which becomes hydrophilic segments after neutralization) and hydrogen-containing phenyl silicone resin (hydrophobic segments) to form an amphiphilic graft copolymer through hydrosilylation, the molecular structure itself is a high molecular surfactant, and a stable nano-dispersion can be formed without the addition of external emulsifiers.
[0059] The coatings obtained in Examples 1-3 can all be air-dried and cured at room temperature, with a surface drying time of 18-25 minutes and a complete drying time of 3.5-5 hours. The coating in Comparative Example 1 requires 45 minutes for surface drying and 8 hours for complete drying. Compared to Comparative Example 1, the complete drying time of the coating obtained by this invention is shortened by 30%-50%, and it can still fully cure when the coating thickness is 100 μm. This indicates that the high oxygen permeability of the organosilicon segments effectively promotes the deep oxidative crosslinking reaction of the coating film, which can significantly improve construction efficiency in industrial applications.
[0060] As shown in Table 1, the pencil hardness of the coatings obtained in Examples 1-3 are H, 2H, and HB, respectively. The hardness of the paint film is related to the phenyl content of the phenyl silicone resin, the type and ratio of alkyd, and the particle size of the product. The castor oil used in Example 2 has a branched hydroxyl structure, a high degree of resin condensation, and a high phenyl content. The product particle size is 180 nm, and the crosslinking point density is the highest, resulting in a paint film hardness of 2H. In contrast, in Example 3, the ratio of alkyd resin to silicone resin is small, the phenyl content is low, the product particle size is 230 nm, and the loose crosslinking network makes the paint film softer and has lower hardness.
[0061] Comprehensive data on adhesion, flexibility, impact resistance, and weather resistance show that the alkyd-modified silicone resin system combines the good adhesion and gloss of alkyd resin with the flexibility and weather resistance of silicone resin, achieving complementary performance and excellent overall properties.
[0062] The water resistance test results showed that the coatings obtained in Examples 1-3 showed no abnormalities such as whitening, blistering, or peeling after immersion in water for 48 hours, while the coating of Comparative Example 1 showed whitening under the same conditions. In the salt water resistance test, the coatings obtained in Examples 1-2 showed no abnormalities after immersion for 72 hours. The coating of Example 3 showed slight discoloration due to its larger particle size and relatively lower degree of crosslinking; while the coating of Comparative Example 1 showed more obvious discoloration under the same conditions. The above comparative results show that, on the one hand, the present invention significantly improves the hydrophobic barrier properties of the coating film through the formation of polysiloxane segments, and on the other hand, it eliminates small molecule emulsifiers and relies on macromolecular amphiphilic copolymers to achieve water dispersion. After film formation, there are no free hydrophilic small molecules remaining, which will not migrate to the surface of the paint film to form hydrophilic channels. Therefore, the water resistance and salt water resistance are superior to commercially available products with added emulsifiers.
[0063] Furthermore, the gloss of the coating in Comparative Example 1 was 72, lower than that of the coatings obtained in Examples 1-3 of this invention. This further confirms the damage to the gloss of the coating film caused by residual external emulsifiers, a problem effectively avoided by the soap-free self-emulsifying design of this invention. Considering key indicators such as water resistance, salt water resistance, and gloss, this invention has significant performance advantages over commercially available products with external emulsifiers.
[0064] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications or equivalent changes made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a soap-free, self-emulsifying alkyd-modified silicone resin, characterized in that, The silicone resin is an amphiphilic graft copolymer, with hydrophilic segments being carboxyl-containing aqueous alkyd segments and hydrophobic segments being hydrogen-containing phenyl silicone resin segments. It can self-emulsify and disperse in water without the addition of external emulsifiers. Includes the following steps: S1: Synthetic aqueous alkyd resin prepolymer with terminal carboxyl groups: Vegetable oil, trimethylolpropane, and catalyst are added to a reaction vessel and heated to 220℃~240℃ under inert gas protection for alcoholysis. After alcoholysis is completed, the temperature is lowered to 160℃~180℃, polyacid anhydride, solvent, and antioxidant are added, and the temperature is raised to 180℃~220℃ for esterification polycondensation. The reaction is stopped when the acid value of the reaction system drops to 50~60mg KOH / g and the viscosity reaches the expected value. S2: GMA end capping introduces aggregateable double bonds: Add a polymerization inhibitor to the aqueous alkyd resin prepolymer obtained in step S1 and stir until homogeneous; mix glycidyl methacrylate with the catalyst and add it dropwise to the reaction system, keep the reaction at 100-110℃, and stop the reaction when the acid value drops to below 10mg KOH / g to obtain GMA-terminated aqueous alkyd resin. S3: Hydrosilylation grafting reaction: The GMA-terminated waterborne alkyd resin obtained in step S2 was dissolved in a solvent, and hydrogen-containing phenyl silicone resin and platinum catalyst were added. The mixture was heated to 80℃~120℃ to carry out a hydrosilylation reaction. After the reaction was completed, the solvent was removed, and a neutralizing agent and deionized water were added to carry out a phase inversion dispersion to obtain a soap-free self-emulsifying alkyd modified silicone resin dispersion. In this step, the Si-H bond at 2160 cm⁻¹ is tracked using infrared spectroscopy. -1 The C=C bond is located at 1640 cm. -1 The disappearance of the characteristic peak determines the reaction endpoint.
2. The preparation method according to claim 1, characterized in that, The vegetable oil mentioned in step S1 is either linseed oil or dehydrated castor oil.
3. The preparation method according to claim 1, characterized in that, The catalyst mentioned in step S1 is lithium hydroxide, and its addition amount is 0.01% to 0.05% of the total mass of the reactants.
4. The preparation method according to claim 1, characterized in that, The method for determining the endpoint of alcoholysis in step S1 is as follows: take the alcoholysis solution and 87% ethanol and mix them at a mass-volume ratio of 1:5 to 1:
7. When the mixture becomes transparent and there is no layering, the alcoholysis is complete.
5. The preparation method according to claim 1, characterized in that, The polybasic acid anhydride mentioned in step S1 is a mixture of phthalic anhydride and trimellitic anhydride; the mass ratio of vegetable oil, trimethylolpropane, phthalic anhydride and trimellitic anhydride is 30-45:25-35:15-25:5-12.
6. The preparation method according to claim 1, characterized in that, The solvent mentioned in step S1 is xylene, and its addition amount is 3% to 8% of the total mass of the reactants; the antioxidant is either triphenyl phosphite or hydroquinone, and its addition amount is 0.05% to 0.2% of the total mass of the reactants.
7. The preparation method according to claim 1, characterized in that, The reaction endpoint in step S1 is a number-average molecular weight of 900–1300 as determined by gel permeation chromatography.
8. The preparation method according to claim 1, characterized in that, The polymerization inhibitor mentioned in step S2 is p-hydroxyanisole, and its addition amount is 0.1% to 0.5% of the mass of glycidyl methacrylate; the catalyst is N,N-dimethylbenzylamine, and its addition amount is 0.1% to 0.5% of the total mass of the aqueous alkyd resin prepolymer obtained in step S1; the addition amount of glycidyl methacrylate is 1.0 to 1.2 times the number of carboxyl groups in the alkyd resin prepolymer obtained in step S1.
9. The preparation method according to claim 1, characterized in that, The hydrogen content of the hydrogen-containing phenyl silicone resin mentioned in step S3 is 0.1wt% to 1.0wt%, the phenyl content is 10wt% to 40wt%, and the molar ratio of C=C in Si-H and GMA-terminated waterborne alkyd resin is 1.0 to 1.5:1.
0.
10. The preparation method according to claim 1, characterized in that, The neutralizing agent mentioned in step S3 is either triethylamine or 2-amino-2-methyl-1-propanol, with a neutralization degree of 70% to 100%.
11. A soap-free, self-emulsifying alkyd-modified silicone resin coating, characterized in that, The mixture comprises a soap-free self-emulsifying alkyd modified silicone resin dispersion prepared by the method according to any one of claims 1-10, a drying agent, a defoamer, a wetting and dispersing agent, a pigment and / or filler, a thickener, and deionized water; wherein the mass ratio of the soap-free self-emulsifying alkyd modified silicone resin dispersion to deionized water is 100:5-20.
12. The coating according to claim 11, characterized in that, The drying agent is one or more combinations of cobalt isooctanoate, zirconium isooctanoate, calcium naphthenate, and zinc isooctanoate, and its addition amount is 0.2% to 1% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion; the defoamer is one of polyether-modified polysiloxane defoamer or non-silicone defoamer, and its addition amount is 0.1% to 0.5% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion; the wetting and dispersing agent is one of nonionic, anionic, or polymeric wetting and dispersing agents. The additive is 0.3% to 1% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion; the pigment and / or filler is one or more of titanium dioxide, iron oxide red, talc, and precipitated barium sulfate, and its addition amount is 10% to 40% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion; the thickener is one of cellulose ethers, alkali-swellable thickeners, or polyurethane thickeners, and its addition amount is 0.1% to 0.5% of the mass of the soap-free self-emulsifying alkyd modified silicone resin dispersion.
13. A method for preparing the coating as described in claim 12, characterized in that, The process includes the following steps: mixing a soap-free self-emulsifying alkyd modified silicone resin dispersion with pigments and / or fillers, wetting and dispersing agents, and a portion of deionized water, and grinding to a fineness ≤30μm; adding a drier, defoamer, thickener, and the remaining deionized water in sequence while stirring, and stirring until homogeneous; adjusting the pH to 7.5–8.5 with a neutralizing agent, filtering the material, and sealing and packaging to obtain an air-drying coating that cures into a film through oxygen oxidation crosslinking at room temperature.
Citation Information
Patent Citations
A kind of waterborne organosilicon modified alkyd resin and preparation method thereof
CN104086761B
A kind of organosilicon modified alkyd resin and preparation method thereof
CN104927039B
Water-based alkyd resin with good weather resistance and water resistance
CN105348498B
An aqueous emulsion of organosilicon-modified alkyd resin and its preparation method
CN107488407B
A low-VOC silicon-modified waterborne alkyd resin and its preparation method
CN110776630B